Application of MEMS technology in anti-electromagnetic radiation maternity clothes: state of the art and future perspectives - Luo, Ye-Cheng; Bai, Qingmei; Skrzypacz, Piotr (Frontiers in Physics, 2025)
This review provides a comprehensive analysis of the application of Micro-Electro-Mechanical Systems (MEMS) technology in anti-electromagnetic radiation maternity wear. The review commences with an elaboration of the electromagnetic shielding principles of traditional materials and the principle of anti-electromagnetic radiation. Subsequently, the role of MEMS in maternity clothing is detailed, including the real-time monitoring of radiation via sensors, the enhancement of fabric shielding through electrospinning and material deposition, and the realization of intelligent functions such as micro-actuators and communication modules. Furthermore, the review considers the optimization of performance, taking into account factors such as electromagnetic shielding, air permeability and comfort. Furthermore, the article addresses the challenges of ensuring comfort and power supply. The article concludes by emphasizing the potential of MEMS in protecting pregnant women and fetuses and proposes future research directions, including an in-depth exploration of the working principles, technical specifications, and performance characteristics of key MEMS components (sensors and micro-actuators), as well as research on the combination and The combination of MEMS technology with existing anti-radiation technologies, such as traditional metal fiber fabrics and nanomaterials, has the potential to yield significant synergistic effects. Furthermore, an in-depth analysis of performance optimization, including durability and washing stability of maternity clothes, is essential. Additionally, the exploration of emerging technologies, such as bubble electrospinning in maternity clothes, could lead to innovative applications in this field.